APPLICATION OF TEAM GAMES TOURNAMENT (TGT) LEARNING MODEL TO STUDENT LEARNING OUTCOMES ON THREE-DIMENSIONAL MATERIAL - Ahmad Nasriadi; Siti Zakia Fadhli; Ully Muzakir (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims to determine the application of the team games tournament(TGT) learning model to the learning outcomes of students on threedimensional material. Students of grade XII MIPA 5 SMA Negeri 9 BandaAceh who were the sample of this study amounted to 29 people selected throughthe purpose sampling technique. The approach used in this study is aquantitative approach with pre-test and post-test research types Data collectiontechniques use tests, observation, and documentation. Through the IndependentSample Test output table, t is calculated |-13.453| > 1.703 t table with sig. (2tailed) is 0.000 (p < 0.005) so it is significant. It can be concluded that theapplication of the team games tournament (TGT) learning model can improvestudent learning outcomes on three-dimensional material.